Serum Homocysteine Could Be Used as a Predictive Marker for Chronic Obstructive Pulmonary Disease: A Meta-Analysis - Chaudhary, Deepti; Sharma, Nidhi; Senapati, Sabyasachi (Frontiers in Public Health, 2019)
Background: Serum homocysteine (Hcy) level inversely related with concentration of folic acid, which is an essential micronutrient for metabolism and energy homeostasis. Serum concentrations of Hcy have been reported to have strong correlation with smoking, which is a major risk factor for pathogenesis of chronic obstructive pulmonary disease (COPD) irrespective of ethnicity and gender. Therefore we performed a systematic review based meta-analysis to evaluate the overall contribution of Hcy in COPD. Method: Published literature on association of serum Hcy with COPD were obtained through conventional web search and eligible literature were selected based on stringent inclusion/exclusion criteria. Continuous variable data was presented as mean and standard deviation. The variable data was analyzed using RevMan 5 statistical tool to evaluate comparative mean differences (MD) with 95 % CI for case-control studies. Result: Four case-control studies met the inclusion criteria for this study. A total of 145 COPD subjects and 107 healthy controls were analyzed. Elevated serum homocysteine concentration was found to induce risk for COPD (MD = 3.05). Conclusion: Molecular role of Hcy in COPD pathogenesis or prognosis is not clear but existing literature suggests that smoking disturbs folic acid metabolism and promotes Hcy accumulation. Our study suggested the contribution of Hcy in COPD pathogenesis, however, large scale prospective cohort study and replication studies with more power are warranted to confirm the results.